Problematika Tata Kelola Benda Sitaan dan Barang Rampasan Negara Pada Rumah Penyimpanan Benda Sitaan Negara Kotabumi Lampung Utara - Dinata, M. Ruhly Kesuma; Abduh, Salis M (Universitas Muhammadiyah Sumatera Barat, 2019)
The existence of a House of Confiscated Objects Storage and State Ransack (Rupbasan) as a place to store evidence related to criminal acts in the criminal justice process has a very important position in the criminal justice system. Explicitly regulated in the Criminal Procedure Code (KUHAP) Article 44 paragraph (1) that “confiscated objects are kept in a state confiscated storage house”. In Kotabumi, North Lampung, there is a Class II State Confiscated Storage House, but its function and role cannot be said to be maximal, because there are still many problems related to the management and maintenance of confiscated objects and State looted goods. The problem of this research is 1) how to manage objects State confiscated and confiscated goods in the state confiscated storage house in Kotabumi, North Lampung, 2) What obstacles are faced in the management of state confiscated objects and confiscated assets at the State confiscated Storage House in Kotabmi, North Lampung, 3) What efforts should conducted in overcoming the constraints of the management of confiscated objects and booty of the State at the State Confiscated Object Storage House in Ktabumi, North Lampung. This study uses a social legal approach by conducting interviews in State Confiscated Objects at Class II Confiscated State Confiscated Houses in Kotabumi, North Lampung. This is done to get more accurate field information. The results showed that Kotabumi Rupbasan had not been able to perform its functions optimally because the relevant agencies did not want to hand over state confiscated objects to be kept in Rupbasan. However, the confiscated objects were managed and used by the relevant legal institutions and then the constraints were limited personnel and limited facilities and infrastructure. Then the efforts of the Head of Rupbasan have submitted an application to the Head of the Regional Office of the Department of Justice for an additional budget for adding warehouses and adding personnel.